INVESTIGATION OF SPECIFIC FEATURES OF THE PRODUCTION OF PRINTED MATERIALS TO THE PROCESS OF PRINTING - Шевченко, Юлия Андреевна (Eastern-European Journal of Enterprise Technologies, 2012)
The aim of the work is the analysis of the peculiarities of the preparation processes of basic consumable materials for printing. Feature of the research is that for research selected only paper.